PRODUCTION AND INDUSTRIAL APPLICATIONS OF PHYCOCYANIN AS A BIOACTIVE PIGMENT - Guardado Yordi, Estela; León Guardado, Lianne de la C.; Pérez Quintana, Manuel Lázaro; Abreu-Naranjo, Reinier; Pérez Martínez, Amaury (Centro Azúcar Journal, 2025)
Introduction: Phycocyanin (PC) is a biopigment obtained mainly from Arthrospira platensis (spirulina), with wide applications in food, cosmetics, and pharmaceutical industries. Its growing demand is due to its safety, chemical stability, and bioactive properties, such as antioxidant and anti-inflammatory activity. However, its extraction and purification face technological and economic challenges that limit its commercial expansion. Objective: To evaluate the potential of PC as a natural biopigment, its industrial applications, extraction and purification methods, and the main challenges and opportunities for its production and commercialization. Materials and Methods: A bibliographic review was carried out in scientific databases such as ScienceDirect, Springer-Nature, SciELO, Taylor & Francis, PubMed, and Google Scholar, considering studies published between 2015 and 2025 on the production, extraction, and applications of PC. Results and Discussion: PC is a viable alternative to synthetic dyes, with applications in various industries. Advanced extraction methods, such as ultrasound, pulsed electric fields, and supercritical fluids, have improved its purity and yield. However, its high cost and lower stability remain limitations. Conclusions: PC is a promising biopigment. Its large-scale implementation will depend on innovations in production, stabilization strategies, and regulations that favor its competitiveness in the global market.